In‐Depth Atomic Mapping of Polarization Switching in a Ferroelectric Field‐Effect Transistor. Issue 14 (1st June 2020) - Li, Xiaoyan; Zhu, Qiuxiang; Vistoli, Lorenzo; Barthélémy, Agnès; Bibes, Manuel; Fusil, Stéphane; Garcia, Vincent; Gloter, Alexandre
Abstract: The ferroelectric control of a Mott transistor is a promising strategy for nonvolatile low‐power electronics. Understanding the fundamental limits of the ferroelectric‐field effect is challenging, as the relevant length scales are restricted to a few atomic planes within the interface. Here, the polarization switching process of a prototypical ferroelectric Mott transistor combining BiFeO3, a ferroelectric material with a large polarization, and (Ca, Ce)MnO3, a charge‐transfer insulator in which a few percent of Ce doping triggers a metal–insulator transition is investigated. While scanning probe microscopy indicates a complete switching of the ferroelectric gate, in‐depth atomic‐scale polarization mapping with scanning transmission electron microscopy reveals incomplete polarization reversal at the interface. Therefore, transport measurements show that the electronic properties of the Mott channel are virtually unchanged by the polarization direction. Nevertheless, in nanometer size areas where interfacial polarization switching occurs, dramatic changes of the electronic properties of (Ca, Ce)MnO3 are revealed. These results indicate how the performance of mesoscale Mott devices is hindered, and at the same time reveal the possibility of nanoscale energy‐efficient Mott transistors. Abstract : Mott transistor combining ferroelectric BiFeO3 and charge‐transfer insulator (Ca, Ce)MnO3 are investigated. Scanning probe microscopy, transport measurements, and scanning transmission electron microscopy reveal the critical impact of interfacial switching properties on the performance of mesoscale Mott devices, a route toward nanoscale energy‐efficient Mott transistors.